Detection of sperm-motivating factor in cervical mucus of ovulatory women - Anjana Ray Chaudhuri; Siddhartha Chatterjee (Al Ameen Medical College, 2013)
Objective: The objective of the present study was to detect the presence of any sperm selecting and / or motivating factor in the cervical mucus (CM) of ovulatory women, which, in turn, might influence pregnancy rate. Materials & Methods: The study was conducted with 190 infertile couples, having indications for moderate seminopathy, enlisted for intra-uterine insemination (IUI), following routine ultrasound and laparoscopic evaluation at our centre, between April 2006 to August 2010. The female partners were in the age group 25-30 years and were randomly divided into 3 groups to receive sperm processed in 3 different methods, with or without CM. Pre and peri-ovulatory CM was subjected to paper electrophoresis on cellulose acetate membrane (CAM) strip, to study the protein band pattern. The different procedures of sperm processing were compared primarily on the basis of sperm motility and quality in the swim-up layer and also the pregnancy outcome following IUI, with due emphasis on improvisation of current laboratory methodologies used in IUI. Results: The use of CM layer alongwith medium for swim-up proved to be the best regarding selection of sperm with maximum motility and normal morphology, as well as the pregnancy outcome. The CM of ovulatory women around ovulation showed the presence of a specific band in electrophoresis. Conclusion: The use of CM in sperm preparation technique proves to be beneficial to patients undergoing IUI.